Pengaruh Work-Life Balance, Motivasi Kerja, Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Bank Perekonomian Rakyat (BPR) Bahteramas Kolaka, Kolaka Utara, Dan Bombana - Ahmad; Milka Pasulu; Nurdin Latif (STIM-LPI Makassar, 2026)
This study aims to analyze the influence of Work-Life Balance, Work Motivation, and Work Discipline on Employee Performance at PT Bank Perekonomian Rakyat (BPR) Bahteramas in Kolaka, North Kolaka, and Bombana. The study employed a quantitative approach using an associative research method. The research population consisted of 60 employees, all of whom were included as the research sample. Data were collected through questionnaires, observation, and literature review. The data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results showed that Work-Life Balance had a positive but insignificant effect on employee performance, with a significance value of 0.363 > 0.05. Work Motivation had a positive and significant effect on employee performance, with a significance value of 0.004 < 0.05, while Work Discipline also had a positive and significant effect on employee performance, with a significance value of 0.002 < 0.05. Simultaneously, Work-Life Balance, Work Motivation, and Work Discipline had a positive and significant effect on employee performance, with a significance value of 0.000 < 0.05. These findings indicate that improving work motivation and discipline is a key factor in enhancing employee performance at PT BPR Bahteramas.